KOMUNIKASI MAHASISWA PEDAGANG KAKI LIMA DI KOTA PEKANBARU - ", Anggara; Firdaus, Muhammad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Student as street vendors are nothing new. The profession of being a peddler is no longer a rare thing and is only done by students who are weak in the economy, because in fact many found students who work as a sidewalk merchant. The purpose of this research is to know self-concept of street hawkers in Pekanbaru city, to know self-interpretation of student of street hawkers in association of campus life in Pekanbaru city and to know communication experience of student of street hawkers in Pekanbaru city.This research uses qualitative research method with phenomenology approach. Research subjects consisted of five students of street vendors in Pekanbaru by using snowball technique. This study uses observation data collection techniques, interviews and documentation. In this study, the authors use interactive data analysis techniques Miles and Huberman.The result of the research shows that student of street hawkers who have positive self concept on the perceptual component is that they feel that they have physical similarity with the students in general, while the negative self concept is related to different physical appearance, looks unattractive and feels the physical condition is low compared to the students who are not traders. The concept of the self is physically meaning the views, thoughts, feelings, and judgments of the street vendor on himself. A person is classified as having a positive self-concept when viewing himself as a confident, responsible, and not desperate, negative component and vice versa. Components of the attitude of street vendors are categorized have positive self-concept among others friendly, fun, comfortable, humorous while the negative self-concept in social self-perception that is afraid to be lowered and feel inferior. Self-interpretation of street vendors on the condition they live as people who do not feel hopeless. Life lived as a street vendor is a thing that makes them feel like an independent child and a fighter. Enjoyable communication experience in the form of support from friends and family, acceptance and good friendship around the environment, and the many praise from the social circle of friends, family and consumers while communication experience is not fun that is in the form of scorn and considered one eye of the campus environment, in a friendship environment, as well as scorn and insult from a friendship or community environment.Keyword : Street hawkers, student, self concept, meaning.